Integrated pest management of citrus greening disease in Mekong Delta for the sustainable production of citrus under severely infested conditions (JIRCAS, 2011)
Contents: Ten years of collaborative research between SOFRI and JIRCAS over citrus greening disease, the development and effective use of pathogen-free seedling as the main component of IPM of citrus greening disease,...